The Effect of Digital Service Quality on Public Satisfaction through Perception of Ease of Use - Atep Suhendar; Tuti Asmala; Ahmad Johan (Program Studi Administrasi Bisnis, 2022)
The main problem in this study is the existence of public complaints related to licensing services in the city of Bandung, especially at the Bandung City Investment and One Stop Integrated Service (DPMPTSP). The research method used is the explanatory method, which is a method to see the relationship or influence between the independent variable and the dependent variable and is also needed to test the hypotheses presented previously. Analysis in data processing using path analysis (path analysis). The results showed that the better the quality of digital services, the better the perception of ease of use (r = 0.818), the perception of ease of use had a positive effect on public satisfaction (R = 73.8%), and the quality of digital services had a positive effect on public satisfaction (R = 74.5%).